O7 Direct expert involvement is not required for providing effective video feedback in the acquisition of clinical skills: a randomised trial. (17th November 2016) - Whitehead, IJ; Phillips, AW; Bookless, LR; Matthan, J; Madhavan, A; Nesbitt, CI; Stansby, G
Abstract : Introduction: Mounting financial and time pressures on universities and healthcare organisations makes providing individual feedback increasingly difficult. Feedback is an important aspect of the learning process and debate prevails over the most effective delivery method. Video technology is increasingly used to assist in clinical skills teaching. This study aims to compare direct expert feedback (DEF), where a recording of the student's performance is reviewed with an expert, to unsupervised video feedback (UVF), where a student compares their recorded performance to an expert video, in order to improve feedback provision in clinical skills teaching. Methods: A randomised blind trial comparing DEF with UVF to assess performance improvement in simulated cannulation, urinary catheterisation and suturing was conducted at Newcastle Medical School. Each clinical skill was assessed by providing students with a standardised lecture before recording them performance the skill. Students were randomised to DEF or UVF and were recorded re-performing the skill. Two blinded experts scored each anonymised pre- and post-feedback recording using a validated proforma for each clinical skill. Results: Seventy-one medical students were recruited. A significant improvement in cannulation scores was noted using UVF compared to scores using DEF (9.5% vs 4.3%, p = 0.44). Students demonstrated a 13.2% improvement in their suturing scores with UVF and a 15.6% improvement with DEF (p = 0.54). Catheterisation scores improved with both feedback modalities (UVF 8.9%, DEF 8.7%, p = 0.96). A significant improvement from baseline scores was demonstrable in every case (p < 0.5). Conclusion: Video feedback provides significant improvement in the acquisition of clinical skills in novices. There is no significant benefit from individual expert involvement when utilising video feedback. Providing students with their recorded performance and a standardised expert video allows them to develop clinical skills at their own pace and may ease demand on faculty.